2019
DOI: 10.1002/jwmg.21771
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Use and Survivorship of Translocated Wild‐Caught Texas Horned Lizards

Abstract: The Texas horned lizard (Phrynosoma cornutum), a state threatened species in Texas, USA, appears to be declining throughout much of its distribution. Because of popular interest in restoring lizard populations, we conducted a 3‐year radio‐telemetric study to evaluate the feasibility of reintroducing Texas horned lizards into previously occupied areas with suitable habitat characteristics. We translocated lizards from natural populations in western Texas to the McGillivray and Leona McKie Muse Wildlife Manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
(35 reference statements)
1
10
0
Order By: Relevance
“…Preliminary analyses of home range sizes for individuals with >5, >10, and >20 recorded capture events showed no statistical difference in home range size estimation; therefore, we chose to be inclusive in range size estimation by including all individuals with >5 recorded capture events using 95% MCPs (Fig. 4; Miller et al 2020). Average home range areas increased ontogenetically with body size.…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary analyses of home range sizes for individuals with >5, >10, and >20 recorded capture events showed no statistical difference in home range size estimation; therefore, we chose to be inclusive in range size estimation by including all individuals with >5 recorded capture events using 95% MCPs (Fig. 4; Miller et al 2020). Average home range areas increased ontogenetically with body size.…”
Section: Resultsmentioning
confidence: 99%
“…Relatively few published studies have used soft release in conjunction with the translocation of lizard species. However, Miller et al [ 17 ] reported that soft-released adult Texas horned lizards had similar movement and survival rates to those reported in the literature for resident animals. Another study using soft release with jeweled geckos ( Naultinus gemmeus ) reported that soft release reduced post-release dispersal movements [ 15 ].…”
Section: Discussionmentioning
confidence: 89%
“…Many translocated animals immediately attempt to return to their site of capture, and animals confined in soft release pens often display increased movement around the periphery of the pen for some period of time; it has been suggested that releasing animals from pens after they cease this behavior might be beneficial [ 12 ]. Soft release often allows animals to develop, practice, and display natural behaviors, such as foraging, mating, thermoregulating, and burrowing, and has proven effective for a number of successful translocation projects [ 13 , 14 , 15 , 16 ] including, recently, for the Texas horned lizard ( Phrynosoma cornutum ; [ 17 ]). For example, gopher tortoises ( Gopherus polyphemus ) that were soft-released in South Carolina moved shorter distances and experienced higher survival upon release than individuals that were hard-released [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Texas horned lizards are known to have a multitude of predators including snakes, predatory lizards, birds, rodents, canids, and felids (Sherbrooke, 2003). Their low annual survival rate (8.9%–54%) is also often attributed to high predation pressure (Endriss et al., 2007; Fair & Henke, 1999; Miller et al., 2020).…”
Section: Introductionmentioning
confidence: 99%